2021
DOI: 10.1186/s13018-021-02213-y
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of lncRNA and mRNA based on expression microarray profiling reveals different characteristics of osteoarthritis between Tibetan and Han patients

Abstract: Background Osteoarthritis (OA) is thought to be the most prevalent chronic joint disease, especially in Tibet of China. Here, we aimed to explore the integrative lncRNA and mRNA landscape between the OA patients of Tibet and Han. Methods The lncRNA and mRNA expression microarray profiling was performed by SurePrint G3 Human Gene Expression 8x60K v2 Microarray in articular cartilage samples from OA patients of Han nationality and Tibetans, followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…By comprehensive analysis of mRNA and lncRNA, Luo et al revealed different features of OA between Han population and Tibetan patients. Specifically, 117 lncRNAs (49 upregulated and 68 downregulated) and 297 mRNAs (158 upregulated and 139 downregulated) had differently expressed in the cartilage of Tibetans compared with those of Han patients (Luo et al, 2021). RNA-sequencing was performed to identify the changed expression of mRNA and lncRNAs in between 5 osteoarthritic synovium samples and 5 healthy tissues.…”
Section: Microarray and Bioinformatics Analyses For Measuring Lncrnas...mentioning
confidence: 99%
“…By comprehensive analysis of mRNA and lncRNA, Luo et al revealed different features of OA between Han population and Tibetan patients. Specifically, 117 lncRNAs (49 upregulated and 68 downregulated) and 297 mRNAs (158 upregulated and 139 downregulated) had differently expressed in the cartilage of Tibetans compared with those of Han patients (Luo et al, 2021). RNA-sequencing was performed to identify the changed expression of mRNA and lncRNAs in between 5 osteoarthritic synovium samples and 5 healthy tissues.…”
Section: Microarray and Bioinformatics Analyses For Measuring Lncrnas...mentioning
confidence: 99%
“…Moreover, numerous lncRNAs are differentially expressed in human OA cartilage ( Abbasifard et al, 2020 ). LncRNA-mRNA co-expression analysis has revealed a remarkable relationship, wherein OTOA may play a critical role in the differential mechanisms of OA progression between Tibetan and Han Chinese populations ( Luo et al, 2021 ). LncRNA-derived LINC00652 can exert biological functions by co-expression with prognostic genes ( INSL3 , SNAP91 , and REN ) and lipid metabolism-related genes ( MIA2, APOA1 ).…”
Section: Herv and Solitary Ltr Elements Are Implicated In Various Hum...mentioning
confidence: 99%